2004
DOI: 10.4067/s0717-92002004000200007
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la roturación del suelo y fertilización con fósforo en el crecimiento inicial de plantaciones de Pinus taeda, en suelos rojos del Noreste de la provincia de Corrientes, Argentina

Abstract: Efectos de la roturación del suelo y fertilización con fósforo en el crecimiento… 69 BOSQUE 25(2): 69-76, 2004 NOTA TECNICA Efectos de la roturación del suelo y fertilización con fósforo en el crecimiento inicial de plantaciones de Pinus taeda, en suelos rojos del Noreste de la provincia de Corrientes, Argentina*

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
1
0
3
Order By: Relevance
“…Vários estudos na América do Sul e no sul dos EUA têm relatado aumentos no crescimento de Pinus taeda em razão da fertilização no plantio (Fernández et al, 1999;2000;Bekele et al, 2003;Ibañez et al, 2004;Vogel et al, 2005;Fox et al, 2007;Everett & PalmLeis, 2009;Faustino et al, 2011;. Contudo, os estudos sobre as árvores jovens e de curto prazo não são adequados para determinar a absorção de nutrientes ao longo do tempo, pois essas podem não atingir o crescimento e as taxas de absorção comparáveis com os dos plantios mais maduros (Bekele et al, 2003).…”
Section: Introductionunclassified
“…Vários estudos na América do Sul e no sul dos EUA têm relatado aumentos no crescimento de Pinus taeda em razão da fertilização no plantio (Fernández et al, 1999;2000;Bekele et al, 2003;Ibañez et al, 2004;Vogel et al, 2005;Fox et al, 2007;Everett & PalmLeis, 2009;Faustino et al, 2011;. Contudo, os estudos sobre as árvores jovens e de curto prazo não são adequados para determinar a absorção de nutrientes ao longo do tempo, pois essas podem não atingir o crescimento e as taxas de absorção comparáveis com os dos plantios mais maduros (Bekele et al, 2003).…”
Section: Introductionunclassified
“…Positive responses have been reported regarding phosphate fertilization in Pinus taeda, mainly on effect on plant growth in the southern USA, going from a volume of 0.0196 m 3 tree -1 in control, to 0.0286 m 3 tree -1 when subjected to fertilization of 58 kg P ha -1 (EVERETT; PALM-LEIS, 2009). Ibañez et al (2004), in Argentina, found an increase in the yield factor of 16.4% (2,178.4 cm 3 plant -1 ) in the second year after planting, when the plants were subjected to 120 g P plant -1 . Currently, applications of large amounts of phosphate fertilizers in forest stands with Pinus are recommended, mainly for the positive response in plant growth (FOX et al, 2007), since large amounts of the nutrient are exported from the site via forest harvesting (STAHL et al, 2017).…”
Section: Fertilization and Nutrition Response Of Pinusmentioning
confidence: 95%
“…Las mismas variables se volvieron a medir al finalizar la primera temporada de crecimiento (primera semana de mayo 2006), y con ellas se estimó el factor de productividad (FP, cm 3 planta -1 ), que es el resultado de DAC 2 * AT/100 (Ibáñez et al 2004).…”
Section: Métodosunclassified